Cyclic Peptide-Gadolinium Nanoparticles for Enhanced Intracellular Delivery - Amir Nasrolahi Shirazi; Shang Eun Park; Shirin Rad; Luiza Baloyan; Dindyal Mandal; Muhammad Imran Sajid; Ryley Hall; Sandeep Lohan; Khalid Zoghebi; Keykavous Parang; Rakesh Kumar Tiwari (MDPI AG, 2020)
A cyclic peptide containing one cysteine and five alternating tryptophan and arginine amino acids [(WR)5C] was synthesized using Fmoc/tBu solid-phase methodology. The ability of the synthesized cyclic peptide to produce gadolinium nanoparticles through an in situ one-pot mixing of an aqueous solution of GdCl3 with [(WR)5C] peptide solution was evaluated. Transmission electron microscopy showed the formed peptide-Gd nanoparticles in star-shape morphology with a size of ~250 nm. Flow cytometry investigation showed that the cellular uptake of a cell-impermeable fluorescence-labeled phosphopeptide (F'-GpYEEI, where F' = fluorescein) was approximately six times higher in the presence of [(WR)5C]-Gd nanoparticles than those of F'-GpYEEI alone in human leukemia adenocarcinoma (CCRF-CEM) cells after 2 h incubation. The antiproliferative activities of cisplatin and carboplatin (5 µM) were increased in the presence of [(WR)5C]-GdNPs (50 μM) by 41% and 18%, respectively, after 72-h incubation in CCRF-CEM cells. The intracellular release of epirubicin, an anticancer drug, from the complex showed that 15% and 60% of the drug was released intracellularly within 12 and 48 h, respectively. This report provides insight about using a non-toxic MRI agent, gadolinium nanoparticles, for the delivery of various types of molecular cargos.